2013
DOI: 10.1007/s11103-013-0130-4
|View full text |Cite
|
Sign up to set email alerts
|

A double SORLIP1 element is required for high light induction of ELIP genes in Arabidopsis thaliana

Abstract: Promoter elements that contribute to high light (HL) induction of the Arabidopsis ELIP1 gene were defined using a transgenic promoter-reporter system. Two adjacent SORLIP1 elements (double SORLIP1, dSL) were found to be essential for HL induction of a GUS reporter gene. The dSL element was also found to be essential for HL induction conferred by the ELIP2 promoter. SORLIP1 elements were enriched in ELIP promoters throughout the plant kingdom, and showed a clade-specific pattern of gain or loss that suggested f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 42 publications
(38 reference statements)
1
9
0
Order By: Relevance
“…In our study, single SORLIP enhanced the luciferase activity compared with dark control and, surprisingly, the duplicated SORLIP increased the luciferase activity enormously. This result supports the result of Alvarez‐Canterbury et al that a double SORLIP1 is required for HL induction of ELIP genes in Arabidopsis . Because duplicated SORLIP is a stronger synthetic promoter than the native 400 bp LIP promoter fragment (Fig 5C), it is highly useful for overexpression of protein(s) under HL.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In our study, single SORLIP enhanced the luciferase activity compared with dark control and, surprisingly, the duplicated SORLIP increased the luciferase activity enormously. This result supports the result of Alvarez‐Canterbury et al that a double SORLIP1 is required for HL induction of ELIP genes in Arabidopsis . Because duplicated SORLIP is a stronger synthetic promoter than the native 400 bp LIP promoter fragment (Fig 5C), it is highly useful for overexpression of protein(s) under HL.…”
Section: Discussionsupporting
confidence: 91%
“…GT‐1 binding motif is also activated by phytochrome, the red/far‐red light photoreceptor , and salt . Interestingly, the LIP promoter is activated by high salt . Therefore it might be interesting to test the salt stress for the GT binding motif.…”
Section: Discussionmentioning
confidence: 99%
“…Photosynthesis genes were observed to be downregulated between these stages (Fig. 8 ), thus activation via these elements may be reduced during the studied period [ 47 , 49 , 50 ]. The ABFs element is enriched in promoters of genes declining in expression throughout the cotyledon timecourse, and is a G-box variant implicated in ABA response and targeted by bZIP transcription factors [ 51 ] (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Both genes are also activated by HL in part through a blue light receptor, CRYPTOCHROME1 (CRY1; Kleine et al, 2007). Promoter analyses have demonstrated that regulatory elements found in ELIP1 and ELIP2 (designated as ELIP1 double SORLIP1 [novel sequences overrepresented in light-induced promoters] and ELIP2 double SORLIP1) are indispensable for activation by HL (Rus Alvarez-Canterbury et al, 2014).…”
mentioning
confidence: 99%